Any value in a specialist review of liver biopsies? Conclusions of a 4‐year review. Issue 2 (15th March 2016) - Paterson, Anna L; Allison, Michael E D; Brais, Rebecca; Davies, Susan E
Abstract : Aims: Liver pathology is a challenging subspeciality, with histopathologists frequently seeking specialist opinions. This study aims to determine the impact of specialist reviews on the final diagnosis and patient management. Methods and results: Agreement with the initial reporting centre in the histopathological diagnosis of 1265 liver biopsies was determined. The nature of differences was explored in more depth for 103 discrepant cases. Differences in the histopathological interpretation were present in 749 of 1265 (59%) biopsies, of which 505 of 749 (67%) were predicted at the time of reporting to impact upon patient management. Agreement was good in cases with chronic viral hepatitis, fatty liver disease, malignancy and minimal pathological changes, while diagnostic differences occurred in more than 70% with biliary disease, autoimmune hepatitis or vascular/architectural changes. A clinical review of a subset of reports with histopathological differences predicted changes in patient management in 63 of 103 (61%). Conclusions: Clinically significant differences in liver biopsy interpretation between local pathologists and subspecialists are common. Diagnoses with frequent discrepancies, such as biliary disease, may benefit from a specialist review as standard when diagnosed initially, while cases requiring specialist advice from disease subgroups where discrepancies are less common, such as chronic viral hepatitis, could be selected during the clinicopathological conference process.